Mutations in pfmdr1 Modulate the Sensitivity of Plasmodium falciparum to the Intrinsic Antiplasmodial Activity of Verapamil - Hayward, Rhys (American Society for Microbiology, 2005)
As well as having the ability to reverse chloroquine resistance in the human malaria parasite Plasmodium falciparum, verapamil has itself an innate antiplasmodial activity. We show here that mutations in Pgh1, the product of the malaria parasite's pfmdr1 gene, influence the parasite's susceptibility to the toxic effects of verapamil.